A NIPAM–Zwitterion Copolymer: Rheological Interpretation of the Specific Ion Effect on the LCST. Issue 11 (22nd April 2014) - Obiweluozor, Francis O.; GhavamiNejad, Amin; Hashmi, Saud; Vatankhah‐Varnoosfaderani, Mohammad; Stadler, Florian J.
<x xml:space="preserve">Abstract</x> The effect of various cations and anions on the ability to shield the electrostatic interaction between charged copolymers containing a non‐ionic moiety (N‐isopropylacrylamide (NIPAM)) is explored. The Hofmeister series, first noted in 1888, ranks the relative influence of ions on the physical behavior of a wide variety of aqueous processes ranging from colloidal assembly to protein folding. The viscoelastic behavior of a poly(NIPAM‐co‐Zw10%) solution as a function of ionic strength in the presence of different ions is rheologically investigated. The obtained copolymer exhibits a thermoresponsive behavior, with tunable lower critical solution temperature (LCST) ranging from 28 to 33 °C. The viscosity change specifically demonstrates the effectiveness of the low‐molecular‐weight ions in weakening the inter‐/intramolecular electrostatic crosslinks among the sulfobetaine chain and in enhancing the hydration of the macromolecule. The effectiveness of the anions follows the Hofmeister series while that of the cations follows the reversed Hofmeister series, as demonstrated by Collins' concept of "matching water affinity, " due to presence of a sulfobetaine group in the chains. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>